1998
DOI: 10.1093/treephys/18.11.769
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal conductance, growth and root signaling in Betula pendula seedlings subjected to partial soil drying

Abstract: Seedlings of Betula pendula Roth were grown with their root systems separated between two soil compartments. Four treatments were imposed: (i) adequate irrigation in both compartments (WW, controls); (ii) adequate irrigation in one compartment and drought in the other compartment (WD); (iii) drought in both compartments (DD); and (iv) half of the root system severed and the remainder kept well-watered (root excision, RE). Predawn leaf water potential, stomatal conductance, soil-to-leaf specific hydraulic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…Betula pendula followed the same pattern as Alnus glutinosa and has also been considered to be isohydric (Robson et al 2014). The decrease in root biomass in Alnus glutinosa and Betula pendula due to drought is in accordance with what is commonly observed in broad leaf species (Chiatante et al 2006;Fort et al 1998). In contrast, Fagus sylvatica in monoculture showed no tendency towards a decrease in biomass.…”
Section: Biomass Allocationsupporting
confidence: 73%
See 2 more Smart Citations
“…Betula pendula followed the same pattern as Alnus glutinosa and has also been considered to be isohydric (Robson et al 2014). The decrease in root biomass in Alnus glutinosa and Betula pendula due to drought is in accordance with what is commonly observed in broad leaf species (Chiatante et al 2006;Fort et al 1998). In contrast, Fagus sylvatica in monoculture showed no tendency towards a decrease in biomass.…”
Section: Biomass Allocationsupporting
confidence: 73%
“…In the split root experiment of Fort et al (1998) fine root growth decreased over time in the dry compartment, but not the wet compartment. We were technically unable to measure root production in the gaps as the area is too small for repeated sampling.…”
Section: Fine Rootsmentioning
confidence: 86%
See 1 more Smart Citation
“…Increased xylem sap ABA concentration was considered as a potential cause of the observed decrease in stomatal conductance as shown in several studies (Davies et al, 2000;Stoll et al, 2000;Liu et al, 2001). However, this response can vary among species as demonstrated by Fort et al (1997Fort et al ( , 1998 working with seedlings of young oak and Betula pendula, who did not find an increase of ABA concentration in xylem sap originated in the roots under PRD conditions. A chemical signal from dehydrating roots leading to a change in apoplastic ABA content in leaves may be responsible for increased stomatal closure under PRD (Holbrook et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PRD practice has been successfully tested on a range of crops, especially tree crops, including apples [17], passion fruit [18], grapevines [19][20][21], oak [22], birch [23], and olive trees [24,25]. The results from several studies showed that crops under PRD yielded better than under DI when the same amount of water is applied, indicating higher water use efficiency (WUE) and even better fruit quality [26].…”
Section: Introductionmentioning
confidence: 99%